A TEG-based waste heat recovery system for atmospheric pressure plasma jets: Model prediction and experimental verification. (5th May 2021) - Huang, Mei-Jiau; Lin, Yu-Hsuan; Hsu, Ping-Chia; Juang, Jia-Yang
Highlights: An APPJ is made smart without consuming extra power. The operating temperature and the ambient air quality are self-monitored. TEGs to convert waste heat of APPJ into electricity for the monitoring system. A compact thermal model is built for prediction and optimization. Machines with high waste heat can be made smart in a similar way. Abstract: We propose a use of thermoelectric power generators (TEGs) to recover waste heat from an atmospheric pressure plasma jet (APPJ) and convert it into electricity for driving a multi-functional monitoring system which monitors the operating temperature of the APPJ itself and the air quality in its surroundings. For design and optimization, a use of the compact thermal model is also proposed. Detailed and important considerations are thoroughly addressed in this study. Model parameters are first calibrated by using some experimental data and then employed for predicting not only the power generation but also the detailed temperature distribution for the purpose of the APPJ itself. With only two commercial thermoelectric chips connected electronically in series, the system is able to produce an open-circuit voltage as high as 8 V and generate a power sufficiently high to drive the monitoring system (1 W and 0.18 A). Such a device and the associated modelling tool can be easily extended to other machines with high waste heat to be self-monitored or to be smart without consuming extra power.